Effect of Anti-Pronation Athletic Tape Types: A Randomized Crossover Trial on Ankle Strength, Gait Parameters, and Balance Control Ability in Women with Flexible Flat Feet - Sang-Young Park; Seong-Gil Kim (Applied Sciences, 2025)
Athletic Tape is widely used as an immediate and cost-effective intervention for flexible flat feet, offering a practical alternative to orthotic devices and exercise therapies. This study aimed to compare the effects of low-dye and anti-pronation taping (elastic and inelastic) on ankle strength, gait parameters, and balance control in women with flexible flat feet. Thirty women were evaluated under four conditions: no taping, low-dye taping, elastic anti-pronation taping, and inelastic anti-pronation taping. Each condition was tested at 3-day intervals. Outcome measures included ankle muscle strength, step length, stride length, balance control ability assessed using the Romberg and limits of stability tests. Repeated-measures analysis of variance and post hoc least significant difference analyses were used to determine statistical significance. Additionally, effect sizes (η2) were calculated for the primary outcomes. Dorsiflexion strength significantly improved with elastic taping (p < 0.05). Step length increased with both elastic and inelastic taping, whereas stride length improved only with elastic taping. All taping methods significantly reduced the limits of stability compared with the no-taping condition (p < 0.05). Athletic Tape interventions, especially elastic anti-pronation taping, may reduce excessive foot pronation and improve ankle strength and gait performance in women with flexible flat feet.